Broadly neutralizing antibody-mediated protection of macaques against repeated intravenous exposures to simian-human immunodeficiency virus. (1st August 2021) - Garber, David A.; Guenthner, Patricia; Mitchell, James; Ellis, Shanon; Gazumyan, Anna; Nason, Martha; Seaman, Michael S.; McNicholl, Janet M.; Nussenzweig, Michel C.; Heneine, Walid
Abstract : Objective: The opioid epidemic has increased parentally acquired HIV infection. To inform the development of a long-acting prevention strategy, we evaluated the protective efficacy of broadly neutralizing antibodies (bNAbs) against intravenous simian-human immunodeficiency virus (SHIV) infection in macaques. Design: Five cynomolgus macaques were injected once subcutaneously with 10-1074 and 3BNC117 (10 mg each kg −1 ) and were repeatedly challenged intravenously once weekly with SHIVAD8-EO (130 TCID50 ), until infection was confirmed via plasma viral load assay. Two control macaques, which received no antibody, were challenged identically. Methods: Plasma viremia was monitored via RT-qPCR assay. bNAb concentrations were determined longitudinally in plasma samples via TZM-bl neutralization assays using virions pseudotyped with 10-1074-sensitive (X2088_c9) or 3BNC117-sensitive (Q769.d22) HIV envelope proteins. Results: Passively immunized macaques were protected against a median of five weekly intravenous SHIV challenges, as compared to untreated controls, which were infected following a single challenge. Of the two bNAbs, 10-1074 exhibited relatively longer persistence in vivo . The median plasma level of 10-1074 at SHIV breakthrough was 1.1 μg ml −1 (range: 0.6–1.6 μg ml −1 ), whereas 3BNC117 was undetectable. Probit modeling estimated that 6.6 μg ml −1 of 10-1074 in plasma corresponded to a 99% reduction in per-challenge infection probability, as compared to controls. Conclusions: Significant protection against repeated intravenous SHIV challenges was observed following administration of 10-1074 and 3BNC117 and was due primarily to 10-1074. Our findings extend preclinical studies of bNAb-mediated protection against mucosal SHIV acquisition and support the possibility that intermittent subcutaneous injections of 10-1074 could serve as long-acting preexposure prophylaxis for persons who inject drugs. Abstract : Supplemental Digital Content is available in the text